Nanodesign : Some basic questions - Schommers, Wolfram (Singapore World Scientific, 2014)
The book explores fundamental questions in nanotechnology, focusing on the design and manipulation of matter at the nanoscale. It discusses conceptual, theoretical and philosophical issues related to nanodesign, including structure formation, self-organization, limits of miniaturization, and the relationship between physical laws and technological possibilities.
Includes bibliographical references and index
Keywords: Cơ bản - Vật lý